Modelagem Dinâmica OO: Uma Análise Comparativa de Técnicas - Reinoso, Guillermo Bustos; Heuser, Carlos A. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1995)
In object-oriented systems modeling three perspectives are considered: the static or structural perspective, the dynamic perspective and the functional perspective. Modeling of the static perspective uses established concepts developed in the arca of semantic data modeling. However, there are several different proposals for dynamic modeling of OO systems. This papers reviews some representative approaches and compares them by several criteria.